2014
DOI: 10.1063/1.4871441
|View full text |Cite
|
Sign up to set email alerts
|

Sphere-plate Casimir interaction in (D + 1) -dimensional spacetime

Abstract: In this paper, we derive the formula for the Casimir interaction energy between a sphere and a plate in (D + 1)-dimensional Minkowski spacetime. It is assumed that the scalar field satisfies the Dirichlet or Neumann boundary conditions on the sphere and the plate. As in the D = 3 case, the formula is of TGTG type. One of our main contributions is deriving the translation matrices which express the change of bases between plane waves and spherical waves for general D. Using orthogonality of Gegenbauer polynomia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Hence, we find that the ratio is bounded in dimensions for all cases we consider. Therefore, the corrections to the proximity force approximation will not gets larger in higher dimensions, in contrast to the sphere-plate and sphere-sphere interactions, where it is found that the ratio of the next-to-leading order term to the leading order term is proportional to D when D is large [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, we find that the ratio is bounded in dimensions for all cases we consider. Therefore, the corrections to the proximity force approximation will not gets larger in higher dimensions, in contrast to the sphere-plate and sphere-sphere interactions, where it is found that the ratio of the next-to-leading order term to the leading order term is proportional to D when D is large [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The idea of the derivation is to similar to perturbation in quantum field theory. Later the method has been generalized to compute the small separation asymptotic behavior of the Casimir interaction energy in various settings [32,41,42,[44][45][46][47][48][49][50][51].…”
Section: Small Separation Asymptotic Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Various approaches have been proposed to compute the Casimir interaction between two objects in ð3 þ 1Þ-dimensional Minkowski spacetime which can either be classified as the worldline method [15][16][17][18][19], multiple scattering approach [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] or mode summation approach [35][36][37][38]. Generalizing the prescription in [38] to arbitrary dimensions, we have been able to compute the zero temperature Casimir interaction between a sphere and a plate [39] and between two spheres [40] in ðD þ 1Þ-dimensional Minkowski spacetime.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the pioneering work [10], a perturbative machinery has been developed in [11,[44][45][46][47][48][49][50][51][52][53]. We use the same method with necessary modification to the present scenario.…”
Section: The Small Separation Asymptotic Behaviormentioning
confidence: 99%